Hubungan Kecanduan Penggunaan Media Sosial Dengan Gangguan Kualitas Tidur - Lale Srigading Udayanti, Lale Srigading Udayanti; Izza Ahmad Muharis; Jannatul Cahya Admiyanti; Muh Rivandha Islami Yoga Pratama; Lale Justin (Lombok Medical Journal, 2023)
Abstract: Social media addiction is a psychological disorder where an individual spends a lot of time accessing social media. In Indonesia, the number of social media users has increased by 21 million or 12.6% from last year. Social media addiction can cause sleep quality disorders, the brain will translate that exposure to blue light from mobile phones as sunlight during the day which causes sleep quality disorders. Sleep quality is a person's ability to start sleeping easily and maintain sleep well. Keywords: Addictions, social media, distractions, sleep quality